Efficacy and visual outcomes of the foldable capsular buckle scleral buckling in rhegmatogenous retinal detachment - Jiang, Guohua; Lin, Yuan; Chen, Yan; Wu, Huping (Frontiers in Medicine, 2024)
Objective: To investigate the difference in the effectiveness and refraction of the foldable capsular buckle (FCB) in rhegmatogenous retinal detachment (RRD). Methods: Six patients with simple RRD were treated for FCB scleral buckling at Xiamen Eye Center of Xiamen University from October 2023 to February 2024. The parameters assessed included demographic data, clinical data such as preoperative ocular axis, corneal endothelial count, macular foveal thickness, operative time, preoperative and final follow-up intro ocular pressure (IOP), retinal attachment status, and postoperative complications. Refractive change before and after surgery, including sphere, cylinder degree, spherical equivalent, and absolute spherical equivalent difference were compared. Results: All six patients with sound retinal reattachment after FCB scleral buckling, including two men and four women, mean age 41.33 ± 12.40 years old, duration before surgery onset to 7.17 ± 7.16 days, FCB mean operation time 36.67 ± 13.07 minutes, Preoperative IOP mean 13.35±2.64mmHg and mean 21.12±8.09mmHg of final follow-up IOP; there was no significant difference between preoperative IOP and follow-up IOP (P=0.050). The preoperative sphere range was -6.25 + 2.50 D, and the cylinder range was -2.50 + 1.00 D; the absolute spherical equivalent difference before and after was 1.60 ± 1.69 degrees. Conclusion: FCB can achieve retinal reattachment and restore visual function in cases of RRD. The shorter duration of external scleral buckle compression with FCB suggests that FCB scleral buckling holds greater promise in the clinical treatment of RRD caused by retinal tears.